Sleep duration and metabolic syndrome: An updated systematic review and meta-analysis - Xie, Jing; Li, Yun; Zhang, Yajun; Vgontzas, Alexandros N.; Basta, Maria; Chen, Baixin; Xu, Chongtao; Tang, Xiangdong (Sleep medicine reviews, 2021)
We examined the association between self-reported sleep duration and metabolic syndrome (MetS). Data were collected from 36 cross-sectional and 9 longitudinal studies with a total of 164,799 MetS subjects and 430,895 controls. Odds ratios (ORs) for prevalent MetS and risk ratios (RRs) for incident MetS were calculated through meta-analyses of adjusted data from individual studies. Short sleep duration was significantly associated with increased prevalent MetS (OR = 1.11, 95% CI = 1.05–1.18) and incident MetS (RR = 1.28, 95% CI = 1.07–1.53) in cross-sectional and longitudinal studies, respectively. Furthermore, long sleep duration was significantly associated with increased prevalent MetS in cross-sectional studies (OR = 1.14, 95% CI = 1.05–1.23), but not incident MetS (RR = 1.16, 95% CI = 0.95–1.41) in longitudinal studies. Interestingly, the association between long sleep and prevalent MetS was found in sleep duration defined by 24-h sleep (including naps) rather than nighttime sleep. Our findings suggest 1) a “U-shape” relationship between sleep duration and MetS in cross-sectional studies and 2) association between short sleep duration, but not long sleep duration with incident MetS. Future studies should shed light on the underlying mechanisms related to the association between sleep duration and MetS and examine if normalizing sleep duration reduces MetS risk in the general population.